Expression 33: "x" equals cosine left parenthesis, "y" minus "d" , right parenthesis minus 4 left brace, 20 less than "y" less than 47 , right bracex=cosy−d−420<y<47
33
Expression 34: "x" equals cosine left parenthesis, "y" minus "d" , right parenthesis minus 4 left brace, 20 less than "y" less than 47 , right bracex=cosy−d−420<y<47
34
Expression 35: "x" equals cosine left parenthesis, "y" minus "d" , right parenthesis minus 4 left brace, 20 less than "y" less than 47 , right bracex=cosy−d−420<y<47
35
Expression 36: "x" equals cosine left parenthesis, "y" minus "d" , right parenthesis minus 4 left brace, 20 less than "y" less than 47 , right bracex=cosy−d−420<y<47
36
Expression 37: "x" equals cosine left parenthesis, "y" minus "d" , right parenthesis minus 4 left brace, 20 less than "y" less than 47 , right bracex=cosy−d−420<y<47
37
Expression 38: "x" equals cosine left parenthesis, "y" minus "d" , right parenthesis minus 4 left brace, 20 less than "y" less than 47 , right bracex=cosy−d−420<y<47
38
Expression 39: "x" equals 30 left brace, negative 10 less than "y" less than 15 , right bracex=30−10<y<15
39
Expression 40: "y" equals negative 10 left brace, 20 less than "x" less than 30 , right bracey=−1020<x<30
40
Expression 41: "y" equals 15 left brace, 20 less than "x" less than 30 , right bracey=1520<x<30
41
Expression 42: "a" equals 1.2a=1.2
negative 10−10
1010
42
Expression 43: "l" equals negative 4.7 5l=−4.75
negative 10−10
1010
43
Expression 44: "h" equals negative 9.8 5h=−9.85
negative 10−10
1010
44
Expression 45: negative 10 "x" plus "y" squared plus 20 plus "x" squared plus 60 equals 225−10x+y2+20+x2+60=225
45
Expression 46: "y" equals 2 left brace, negative 5 less than "x" less than negative 3 , right bracey=2−5<x<−3
46
Expression 47: "x" equals negative 5 left brace, negative 2 less than "y" less than 2 , right bracex=−5−2<y<2
47
Expression 48: "y" equals negative 2 left brace, negative 5 less than "x" less than negative 3 , right bracey=−2−5<x<−3
48
Expression 49: "x" equals negative 1 left brace, negative 2 less than "y" less than 2 , right bracex=−1−2<y<2
49
Expression 50: "y" equals negative 2 left brace, negative 1 less than "x" less than 1 , right bracey=−2−1<x<1
50
Expression 51: "x" equals 1 left brace, negative 2 less than "y" less than 2 , right bracex=1−2<y<2
51
Expression 52: "y" equals 2 left brace, negative 1 less than "x" less than 1 , right bracey=2−1<x<1
52
Expression 53: "x" equals 3 left brace, negative 2 less than "y" less than 2 , right bracex=3−2<y<2
53
Expression 54: "y" equals 0 left brace, 3 less than "x" less than 5 , right bracey=03<x<5
54
Expression 55: "y" equals 2 left brace, 3 less than "x" less than 5 , right bracey=23<x<5
55
Expression 56: "x" equals 6 left brace, negative 2 less than "y" less than 2 , right bracex=6−2<y<2
56
Expression 57: "y" equals 2 left brace, 6 less than "x" less than 8 , right bracey=26<x<8
57
Expression 58: "y" equals 0 left brace, 6 less than "x" less than 8 , right bracey=06<x<8
58
Expression 59: "x" equals 9 left brace, negative 2 less than "y" less than 2 , right bracex=9−2<y<2
59
Expression 60: "y" equals 0 left brace, 9 less than "x" less than 11 , right bracey=09<x<11
60
Expression 61: "y" equals 2 left brace, 9 less than "x" less than 11 , right bracey=29<x<11
61
Expression 62: "y" equals negative 2 left brace, 9 less than "x" less than 11 , right bracey=−29<x<11
62
Expression 63: "x" equals 12 left brace, negative 2 less than "y" less than 2 , right bracex=12−2<y<2
63
Expression 64: "y" equals negative 2 left brace, 12 less than "x" less than 14 , right bracey=−212<x<14
64
Expression 65: "y" equals 0 left brace, 12 less than "x" less than 14 , right bracey=012<x<14
65
Expression 66: "y" equals 2 left brace, 12 less than "x" less than 14 , right bracey=212<x<14